Offset calibration technique for capacitive transimpedance amplifier used in uncooled infrared detection. (July 2016) - Ahmed, A.S.H.; Aboudina, M.M.; Habib, S.E.D.
Abstract: This paper presents a novel readout circuit of uncooled, bolometer-based, focal plane arrays (FPAs). The offset and flicker noise are the design challenges of microbolometer readout circuits (ROCs). The ROC is not only required to apply careful noise cancellation techniques, but also to be insensitive to process and supply voltage variations. The proposed circuit involves a new offset cancellation technique which overcomes process variations, noise, random, and systematic offset.